2005
DOI: 10.1213/01.ane.0000145012.27484.a7
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane but Not Propofol Preserves Myocardial Function During Minimally Invasive Direct Coronary Artery Bypass Surgery

Abstract: Volatile anesthetics exert cardioprotective properties in experimental and clinical studies. We designed this study to investigate the effects of sevoflurane on left ventricular (LV) performance during minimally invasive direct coronary artery bypass grafting (MIDCAB) without cardiopulmonary bypass. Fifty-two patients scheduled for MIDCAB surgery were randomly assigned to a propofol or a sevoflurane group. Apart from the anesthetics used, there was no difference in surgical and anesthetic management. After det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
3
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 28 publications
0
49
3
6
Order By: Relevance
“…In two studies published recently, late postconditioning with sevoflurane used for sedation after coronary surgery also did not provide reduction of troponin release [19,20]. In our patients, the time of ischaemia (median 11 min) was shorter than reported in studies demonstrating significant cardioprotective effect of volatile anaesthesia for off-pump coronary surgery (> 15 min) [11]. Thus, it is very likely that in our study, the time of ischaemia was not long enough to result in myocardial damage and the cardioprotective effect of desflurane could not manifest itself explicitly.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In two studies published recently, late postconditioning with sevoflurane used for sedation after coronary surgery also did not provide reduction of troponin release [19,20]. In our patients, the time of ischaemia (median 11 min) was shorter than reported in studies demonstrating significant cardioprotective effect of volatile anaesthesia for off-pump coronary surgery (> 15 min) [11]. Thus, it is very likely that in our study, the time of ischaemia was not long enough to result in myocardial damage and the cardioprotective effect of desflurane could not manifest itself explicitly.…”
Section: Discussioncontrasting
confidence: 71%
“…Propofol, when compared to sevoflurane, in patients undergoing off-pump coronary surgery has been shown to be related to deeper left ventricular function compromise and delayed recovery of haemodynamic parameters [11]. Similarly, lower cardiac output after 15 min reperfusion and higher troponin I concentration was observed in off-pump coronary surgery under propofol anaesthesia when com- Table 3.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies (11)(12)(13)(14)(15)(16)18,19) and reviews (21)(22) have appeared in the literature suggesting a cardioprotective effect provided by volatile anesthetics in patients undergoing cardiac procedures. A recent survey (23) conducted in 64 Italian centres, encompassing a total of 34,310 patients undergoing coronary artery bypass graft surgery, showed that risk-adjusted mortality may be reduced by the use of volatile agents.…”
Section: Discussionmentioning
confidence: 99%
“…Кардиопротективные эффекты ингаляционных анесте тиков при операциях на коронарных артериях подтверждены и другими исследованиями [18,19].…”
Section: влияние выбора метода анестезии на исход оперативного леченияunclassified